The construction and phenotypic characterization of mycobacterial mutants deficient in DNA glycosylases - Goosens, Vivianne Jacoba (My University, 2009)
Mycobacterium tuberculosis is an exquisitely adapted intracellular pathogen that encounters hostile, host-derived reactive nitrogen and oxygen intermediates during the course of infection of its human host. These radicals cause DNA damage, which is repaired through various pathways to allow for the continued survival of the organism. Base excision repair (BER) is one such pathway, which depends on DNA glycosylases to identify and excise damaged DNA bases. Formamidopyrimidine DNA glycosylase (Fpg/ MutM/ FAPY) and Endonuclease VIII (Nei) are such enzymes, which both target oxidatively damaged DNA and together, form the Fpg family of DNA glycosylases. Bioinformatic analyses identified two copies each of Fpg and Nei-encoding genes in M. tuberculosis as well as in its non-pathogenic relative, Mycobacterium smegmatis. To understand the role of these multiple glycosylases in the maintenance of genomic integrity and survival of mycobacteria, the genes encoding the four Fpg/Nei glycosylases were individually deleted in M. smegmatis strain mc2155 by homologous recombination. In addition to the four single mutants, double and triple Fpg and Nei glycosylase knockout mutants were generated by sequential gene knockout. When compared to the parental strain, the single and double mutants showed no variation in growth kinetics, no increased sensitivity to hydrogen peroxide and no increase in spontaneous mutation rates. However, a slight increase in frequency of spontaneous C T transition mutations was observed in double knockout mutants compared to the wild type and single mutant strains. These results suggest that these enzymes may be part of an extensive network of enzymes which collectively work to enhance the overall survival of M. smegmatis through the repair of oxidatively damaged DNA.
Keywords: Mycobacteria; DNA glycosylases; DNA repair